Internet of Things based Smart Baby Monitoring System - Zakaria, Nur Zarifah; Muhammad Soomro, Dur (Evolution in Electrical and Electronic Engineering, 2023)
In today's world, taking care of a newborn baby may be quite a struggle for parents who are already juggling a lot of responsibilities at home, such as cleaning or working. In addition, parents who have physical limitations often need additional assistance when it comes to looking after their infant. There are previous projects where a baby monitoring system has also been done. Some of those systems used Raspberry Pi as a microcontroller with temperature, humidity, and microphone. While there is also a similarity in the output and input components between a few previous and current projects such as the Global System for Mobile Communication (GSM) module and temperature sensor the only differing, part is the model of the temperature sensor. Hence, this project of an IoT-based Smart Baby Monitoring system was done to help in decreasing the burden of parents who do chores and works at home. It is possible to reduce some of the burdens that parents have while they are working by using this system, which has a variety of functions such as the ability to monitor temperature, sound, and video. A GSM module is utilized in this system, which makes it possible for the parents to get alerts regarding the status of their infant. The smartphone of the parent is where notifications will be sent. Therefore, a system that is specifically built for babies at home is required to relieve some of the burdens that are placed on parents when they are busy and allow them to be aware of the state of their kids at the same time.